Human Resource Development in Kintom District Government, Banggai Regency, Central Sulawesi Province - Benda, Fuly Prio; Nawawi, Muh; Natsir, Nawawi (Journal of Universal Community Empowerment Provision, 2025)
The objectives to be achieved in this study are to determine and analyze Human Resource Development in the Kintom District Government, Banggai Regency, Central Sulawesi Province. To scientifically measure Human Resource Development in this study using the Human Resource Development theory proposed by Michael Armstrong, which includes the elements: Learning, Education, Development and Training. This research is a type of descriptive research using a qualitative method approach. This research took place in the Kintom District Government, Banggai Regency. Determination of research informants was carried out purposively. The research informants in this study were 7 (seven) informants. This research uses Primary Data and Secondary Data. Data collection was carried out using observation, interview and documentation techniques. Data analysis in this study uses an interactive model, including: Data Condensation, Data Display, and Conclusion Drawing/Verification. Based on the results of research and discussion on Human Resource Development in the Kintom District Government, Banggai Regency. It is concluded that the Learning aspect and Development aspect in human resource development have been implemented optimally. While the Education aspect and Training aspect in human resource development have not been implemented optimally.